Atlantic salmon (Salmo salar) and brown trout (Salmo trutta) differ in their suitability as hosts for the endangered freshwater pearl mussel (Margaritifera margaritifera) in northern Fennoscandian rivers - Salonen, Jouni; Luhta, Pirkko-Liisa; Moilanen, Eero; Oulasvirta, Panu; Turunen, Jarno; Taskinen, Jouni (Freshwater Biology, 2017)
1. European populations of the freshwater pearl mussel (FPM, Margaritifera margaritifera) have widely collapsed, and despite many types of conservation actions the number of successful restoration trials has remained limited. The goal of this study was to find new aspects for the conservation by investigating whether there are population-specific differences in suitability of Atlantic salmon (Salmo salar) and brown trout (S. trutta) as the hosts for the parasitic glochidium larvae of FPM, depending probably on the historical occurrence of these salmonid species in FPM habitats. 2. We studied the potential host specificity both in the field and in laboratory by exposing salmonid fish to FPM glochidia originating from nine populations of different types of streams and rivers within three different large river basins of northern Fennoscandia. 3. The exposures showed remarkable population-specific differences in the host species suitability. In large main channels, previously colonized by Atlantic salmon but most now dammed for hydropower production, the occurrence of FPM glochidia was always highest in salmon. Moreover, the glochidia in salmon were often larger than the conspecifics in brown trout. Conversely, in small tributaries with no salmon history, brown trout was generally the best, or the only suitable, host for FPM. 4. Especially the adaptation of certain FPM populations exclusively on salmon is a considerable finding, which offers – together with the hydropower dam construction and the salmonid fish stocking practices often favouring brown trout – an additional explanation for the collapse of FPM populations living in former Atlantic salmon rivers. 5. Furthermore, this study illustrates the indirect but substantial effects that river damming and changes in fish communities may induce, and emphasize the need to investigate the most suitable host species for each FPM population as the basis for management and conservation actions. peerReviewed